Efficiency Evaluation of Two Domestic Water Treatment Filtration Models (2022)
The World Health Organization (WHO) proposes domestic water treatment as an effective means that contributes greatly to the improvement of water quality in rural areas. The purpose of this study was to evaluate the removal efficiency of two domestic water treatment systems that correspond to the ceramic pot filter and ceramic candle filter under two maintenance conditions. Natural water from the underground well of the University of Boyacá was used, and the evaluated parameters were turbidity, total coliforms, E. coli pH, conductivity, color and the filtration rate. The evaluation time was 46 days, each filter was fed daily with a volume of 7.5 L. The results showed that on the days of the cleaning activities, peaks in turbidity were generated; The filters without maintenance had an effluent with lower values of this parameter with respect to the systems with maintenance. Additionally, the efficiency of these systems for the removal of E. coli was verified. The variation in the filtration rate significantly influences the degree of sustainability of the systems, with maintenance being one of the incident factors, for this reason it is recommended to be carried out weekly, in order to avoid clogging of the pores in both filtration systems.